2016
DOI: 10.1155/2016/4793434
|View full text |Cite
|
Sign up to set email alerts
|

High Dielectric Constant Study of TiO2-Polypyrrole Composites with Low Contents of Filler Prepared byIn SituPolymerization

Abstract: TiO2/polypyrrole composites with high dielectric constant have been synthesized byin situpolymerization of pyrrole in an aqueous dispersion of low concentration of TiO2, in the presence of small amount of HCl. Structural, optical, surface morphological, and thermal properties of the composites were investigated by X-ray diffractometer, Fourier transform infrared spectroscopy, field-emission scanning electron microscopy, and thermogravimetric analysis, respectively. The data obtained from diffractometer and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, plasma proteins or PEI did not show such a characteristic peak contributed (1188 cm −1 ) from PPy. A similar finding in literature showed that the CC stretching vibration in pyrrole ring was observed at the same characteristic peak (1188 cm −1 , Figure c) . Chemical structures of PPy‐PEI NPs and PPy‐PEI‐P NCs were further confirmed by 1 H‐nuclear magnetic resonance (NMR) spectroscopy, and the spectra are shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…However, plasma proteins or PEI did not show such a characteristic peak contributed (1188 cm −1 ) from PPy. A similar finding in literature showed that the CC stretching vibration in pyrrole ring was observed at the same characteristic peak (1188 cm −1 , Figure c) . Chemical structures of PPy‐PEI NPs and PPy‐PEI‐P NCs were further confirmed by 1 H‐nuclear magnetic resonance (NMR) spectroscopy, and the spectra are shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…The study of ferroelectric particles into the conducting polymer matrix has revealed that there is a decrease in conductivity with the increase in the wt % or vol % of the filler [35]. Keeping in view such investigations and focusing the effect of processing conditions on the conductivity of such polymers, the composites using TiO 2 in PPy and TiO 2 -PVA in PPy [36,37] were successfully prepared and characterized exhibiting excellent dielectric behaviour found both at low and high frequencies of the applied electric field (AC). The trend was attributed to the very small particle size in the final composites which offered large surface to volume ratio for high interfacial polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, overall dielectric signature for the PA and copolymer is similar except the fact that the copolymers exhibit intermediate dielectric values at lower frequency compared to the homopolymers. It is worth notifying that the observed dielectric features in these systems are superior to various other conducting polymers complexes based on MEH-PPV hybrid systems as well as conducting polymer-based composite systems [63][64][65], which makes these systems interesting materials for next-generation organo-electronics. Figure 5 shows the TGA profiles of all the PA, P-3-NA and copolymer samples.…”
Section: Electrical Conductivity Comparative Studymentioning
confidence: 98%